DAMPAK LIMBAH PEDAGANG IKAN TERHADAP HARMONI SOSIAL DI DESA APITAIK KECAMATAN PRINGGABAYA - Samsul Hakim (Universitas Hamzanwadi, 2019)
Most of the people in Gubuk Lekok Hamlet in fulfilling the necessities of life make fish traders business as permanent livelihoods, hereditary from their ancestors. So far, researchers see that community activities in running the business have an impact, bad impression and message for a hamlet. Gubuk Lekok Hamlet is known as a smelly, dirty and unpleasant village for anyone who is a newcomer or a visitor. This gave rise to innuendo, labeling or labeling a village and impacting both the environment and social harmony. This research is located in the Apitaik Village of Lubok Gubuk Hamlet. The data collection techniques used are observation, interview and documentation. Furthermore the data is processed using qualitative descriptive analysis methods. From the findings in the field the researchers can report that the behavior of the community as traders (pemindang) fish does not fully reflect healthy behavior. Responds and responses or insinuations from other communities, stigma various kinds of other communities. The people in Lekok Gubuk Hamlet in Apitaik Village ignored each other. The most important thing is they can eat to fulfill their economic needs. Slow sea if conditions like this are left will become Social Disharmonization because of anger, hatred, annoyance and quarrels that occur in the community environment.